PRIMER INFORME DE GOBIERNO 1983 (1983)
CONTENIDO: SECTOR GOBIERNO. -- SECTOR TURISMO. -- SECTOR EDUCATIVO. -- SECTOR SALUD Y SEGURIDAD SOCIAL. -- SECTOR AGROPECUARIO Y FORESTAL. -- SECTOR POLITICA EXTERIOR. -- SECTOR LABORAL. -- SECTOR DESARROLLO URBANO Y ECOLOGIA